Intellectual property rights, foreign direct investment and the shadow economy (2012)
The relationship between intellectual property rights (IPR) protection and foreign direct investment (FDI) continues to pose a challenging puzzle. While several studies have found that these two variables are positively correlated, others have not been able to find conclusive results or have found that the relationship is actually negative. We contend that a partial explanation of these contradictory results resides on institutional differences among host countries. We find that increases in IPR protection encourage FDI in countries in which the shadow (informal) economy represents a relatively small percentage of the country’s economy but it does not produce the same result in countries in which that percentage is relatively large. The size of the shadow economy is determined, in turn, by the quality of institutional variables such as the degree of bureaucracy, the level of corruption, and the extent of confiscatory taxation and political instability. We present empirical evidence supporting the results of our theoretical framework using threshold regression techniques on a sample of 94 countries and data for the 2000 - 2005 period.